ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS PRODUK,CITRA MEREK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KARTU PERDANA INDOSAT OOREDOO (Studi Kasus pada Konsumen Indosat Ooredoo di Semarang) - Nantyas Cahyaningrum, Ajeng; Yoestini, Yoestini (Faculty of Economics and Business Diponegoro University, 2018)
The research is proceeded based on the significant decrease of Indosat Ooredoo’s net profit on 2013 and 2014. The aim of the research is to find out the influence of perception of price (X1), product quality (X2), brand image (X3) and word of mouth (X4) towards the buying decision of Indosat Ooredoo prepaid SIM card in Semarang. The methods of data collection used in this research was a questionnaire to 100 participants spread at Semarang, which has been using Indosat Ooredoo for more than a year. Sampling technique was done by using purposive sampling methods. Data analysis on this research is using multiple linear regression analysis using SPSS for windows. The result of the research shows that the variable of perception of price, product quality, brand image and word of mouth is having a positive and significant influence towards the buying decision of Indosat Ooredoo prepaid SIM card at Semarang. Among the four variables mentioned, product quality was the most influencing variable towards the buying decision. Therefore it is suggested for the company to improve the quality continuously in order to improve the buying decision of Indosat Ooredoo prepaid SIM card.